REKONSTRUKSI SIDIKARA PADA MASYARAKAT BALI SEBAGAI PRAKTEK AJARAN TEOLOGI SOSIAL - I Wayan Sunampan Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Humans as social beings basically cannot be separated from social interaction within society.However, in its development, social values began to change towards a social crisis. This can beseen from the individualistic attitude that began to develop in society. Social values that haveexisted since time immemorial have begun to change. From this, it is necessary to rebuild socialvalues which are also inseparable from religious activities. One of them is sidiikara is an actiontogether in order to achieve an expected goal in accordance with the value of solidarity. Thispaper tries to describe sidikara by using qualitative methods. Qualitative method is a researchmethod in natural situations with data collection methods through observation, interviews,documentation, and literature study. When the data is collected, it is analyzed and then presentedwith a qualitative discrete method. The result of this discussion is that Sidikara is a form of socialvalue that is experiencing a social crisis so that it needs to be reconstructed.. Sidikara is basicallymanifested in forms such as mutual idihin, mutual substitution, mutual tulungin, majenukan, sikaraparid, sikara rojong. All of these are social activities that emphasize togetherness that hasrelevance to the sacred text of Hinduism. The value of Sikara in society needs to be rebuilt so thatit becomes a solution to moral problems